Halal Tourism Industry: Advantages and Challenges in Malaysia - Faridah Hj Hasan; Siti Aisah binti Yusop; Fatin Lina Amirah binti Mohd Idris; Muhammad Izrin Hani bin Mohd Rani; Santi Rahmawati (International Journal of Emerging Issues in Islamic Studies, 2023)
Halal tourism is gaining popularity as it caters to religious demands and Shariah compliance. Malaysia is one of the most favoured travel destinations for Muslim tourists worldwide, providing halal tourism packages. This study aims to explore the halal tourism industry, particularly the advantages and challenges in Malaysia, and reviews the concept of halal tourism, halal destination, halal hotel and halal food. To better understand the halal tourism industry in Malaysia, this research employs secondary qualitative data gathered from various sources, including books, journal articles, newspapers, journal data, and reports. The SWOT and TOWS matrix were used to analyse the data. The finding discusses the advantages and the challenges of halal tourism in terms of halal destinations, halal hotels and halal food in Malaysia, including the statistics. Malaysia's halal tourism sector can develop further to align with the rise of Muslim visitors. Many other nations, with many Muslims and non-Muslims, work to promote halal tourism. This research shed light on the practice of halal tourism industry in Malaysia.